Efek Perbedaan Konsentrasi Bubuk Daun Kelor (Moringa oleifera) Terhadap Peningkatkan Kualitas Fisik Dadih: Effect of Different Concentrations of Moringa Leaf Powder on Improving The Physical Quality Dadih - Raguati, Raguati; Monica, Metha; Afzalani, Afzalani; akhsyar, Mhd saidi akhsyar (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2023)
Dadih or Curd is a fermented product from buffalo milk. The availability of milk buffalo is limited so try replacing it with cow’s milk. This research applies cow's milk to make curd which is enriched with Moringa leaf powder. This research aims to evaluate the level/concentration of Moringa leaf powder which can improve the physical quality of the curd milk cow. This research was arranged in a completely randomized design (CRD) with five treatments of Moringa leaf powder levels which consist of 0%, 0.5%, 1%, 1.5%, and 2%. The data had analyzed with analysis of variance (ANOVA) and different between treatment were analyze with Duncan's tests. The experiment results showed that the addition of Moringa leaf meals in the curd did not difference effect of physical quality of curd cow's milk. The research concluded that the use of Moringa leaf powder of up to 2% can be used in producing of cow's milk curd.